Microstructure and Mechanical Properties of an Underwater Wet Welded Dissimilar Ferritic/Austenitic Steel Joint - Guo, N.; Yang, Z.; Wang, M.; Yuan, X.; Feng, J. (Проблемы прочности, 2015)
EH40 ship steel was underwater wet-welded by shielded metal-arc welding at a depth of 7 m in the open sea, using austenitic electrodes. The microstructure and mechanical properties of the joint were estimated with microhardness measurements, bending and tensile testing, optical microscopy, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The highest microhardness was recorded on the coarse-grained heat-affected zone of the base metal, which displayed a mixed bainite-martensite microstructure, while the welds possessed a fully columnar dendritic austenitic structure. The specimens exhibited higher ultimate strength and elongation in longitudinal tensile tests than in transverse ones. Moreover, the specimens satisfied face bending tests but failed in root bending ones. Hydrogen-induced microcracks, which were observed in a lath martensite layer at the fusion boundary, became the fracture initiation region both in bending and transverse tensile tests. Судостроительная сталь ЕН40 подвергалась дуговой сварке металлическим (аустенитным) электродом мокрым способом под водой на глубине 7 м в открытом море. Микроструктуру и механические свойства шва оценивали по результатам измерения микротвердости, испытаний на изгиб и растяжение с помощью оптической и сканирующей электронной микроскопии, энергодисперсионной рентгеновской спектроскопии. Наиболее высокую микротвердость регистрировали в крупнозернистой зоне термического влияния основного металла, который имел смешанную бейнит-мартенситную микроструктуру, тогда как швы приобрели законченную столбчатую дендритную структуру. Образцы демонстрировали более высокие пределы прочности и удлинение при испытаниях на растяжение в продольном направлении, чем в поперечном. Кроме того, образцы выдержали испытания на изгиб с растяжением внешней стороны шва, но показали неудовлетворительные результаты при растяжении его обратной стороны. Водородное микрорастрескивание, наблюдаемое в реечном мартенситном слое на границе плавления, стало зоной зарождения разрушения при испытаниях на изгиб и растяжение в поперечном направлении.